Factors Associated with the Occurrence of Osteoarthritis: A Path Analysis Evidence from Surakarta, Central Java - Mei Kusumaningtyas; Didik Tamtomo; Bhisma Murti (Journal of Epidemiology and Public Health, 2019)
Background: Musculoskeletal conditions are an important public health problem. The population burden from arthritis is considerable. The implications of this burden are poor quality of life, restrictions in daily activities, and disability. This study aimed to analyze factors associated with the occurrence of osteoarthritis in Surakarta, Central Java, using a path analysis model.Subjects and Method: This was a cross-sectional study conducted at Dr. Moewardi Hospital, Surakarta, Central Java, in June 2018. A sample of 200 patients was selected by fixed disease sampling, consisting of 50 knee OA patients and 150 patients without knee OA. The dependent variable was knee OA. The dependent variables were age, gender, body mass index (BMI), diabetes mellitus, history of injury, and physical activity. Data on knee OA, BMI, and diabetes mellitus status were obtained from medical record. The other variables were measured by questionnaire. The data were analyzed by path analysis.Results: The risk of OA increased with diabetes mellitus (b=1.04; 95% CI= 0.17 to 1.92; p=0.020), older age (b= 4.03; 95% CI= 1.97 to 6.09; p<0.001), and BMI ?25 (b= 1.28; 95% CI= 0.39 to 2.17; p= 0.005). The risk of OA decreased with history of knee injury (b= -0.90; 95% CI= 0.57 to 1.74; p= 0.003) and female (b= -1.19; 95% CI= -2.06 to -0.31; p=0.008). The risk of OA was indirectly affected by physical activity, female gender, and BMI.Conclusion: The risk of OA increases with diabetes mellitus, older age, and BMI ?25, but decreases with history of knee injury and female gender.The risk of OA is indirectly affected by physical activity, female gender, and BMI.Keywords: knee osteoarthritis, sociodemographic factor, diabetes mellitus, path analysisCorrespondence:Mei Kusumaningtyas. Masters Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami 36 A, Surakarta 57126, Central Java. Email: meikusumaningtyas@gmail.com. Mobile : +6285725646444Epidemiology and Public Health (2019), 4(1): 9-19https://doi.org/10.26911/jepublichealth.2019.04.01.02